A novel high pressure column flow reactor for experimental studies of CO2mineral storage - Galeczka, I.; Wolff-Boenisch, Domenik; Jonsson, T.; Sigfusson, B.; Stefansson, A.; Gislason, S. (Pergamon, 2013)
The objective of this study was to design, build, and test a large scale laboratory high pressure columnflow reactor (HPCFR) enabling experimental work on water–rock interactions in the presence of dissolved gases, demonstrated here by CO2. The HPCFR allows sampling of a pressurized gas charged liquid along the flow path within a 2.3 m long Ti column filled with either rock, mineral, and/or glass particles. In this study, a carbonated aqueous solution (1.2 M CO2(aq)) and basaltic glass grains was used. Given the pressure and temperature rating (up to 10 MPa at 90 C) of the HPCFR, it can also be used with different gas and/or gas mixtures, as well as for supercritical fluid applications. The scale of the HPCFR, the possibility of sampling a reactive fluid at discrete spatial intervals under pressure, and the possibility of monitoring the evolution of the dissolved inorganic carbon and pH in situ all render the HPCFR unique in comparison with other columns constructed for studies of water–rock interactions. We hope that this novel experimental device will aid in closing the gap between bench scale reactor experiments used to generate kinetic data inserted into reactive transport models and field observations related to geological carbon sequestration. A detailed description and testing of the HPCFR is presented together with first geochemical results from a mixed H2O–CO2 injection into a basalt slurry whose solute concentration distribution in the HPCFR was successfully modelled with the PHREEQC geochemical computer code.